2005
DOI: 10.3200/aeoh.60.3.119-127
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide-Related Injury Estimation Using ICD-Coded Data: Methodologic Implications for Public Health Surveillance

Abstract: Estimates of unintentional deaths from carbon monoxide (CO) poisoning can be obtained from national mortality data. We explored ways of accurately estimating CO-related deaths from International Classification of Diseases, 9th Revision (ICD-9) coded U.S. mortality data. We evaluated and identified CO-related ICD-9 codes and created five classes of codes for case ascertainment that represented a continuum of the degree of certainty that the ICD-coded death was truly CO-related. We conducted single (underlying) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A major issue related to data reliability is the quality, consistency, and comparability of the reporting mechanisms applied by different countries to collect mortality statistics. Although this review has not been designed to identify in detail the national mechanisms of reporting, it can be concluded that the use of the ICD system often lacks consistency (Ball et al., ). The move from ICD9 to ICD10 in 2002 has lead to an increase in reported CO cases in Austria, while in Spain, the ICD10 implementation no longer enables the identification of mortality exclusively related to CO from the mortality statistics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major issue related to data reliability is the quality, consistency, and comparability of the reporting mechanisms applied by different countries to collect mortality statistics. Although this review has not been designed to identify in detail the national mechanisms of reporting, it can be concluded that the use of the ICD system often lacks consistency (Ball et al., ). The move from ICD9 to ICD10 in 2002 has lead to an increase in reported CO cases in Austria, while in Spain, the ICD10 implementation no longer enables the identification of mortality exclusively related to CO from the mortality statistics.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is to be noted that the transition from ICD9 to ICD10 has caused some changes in the coding system, and thus, some countries show discrepancies between the CO mortality reported according to ICD9 and ICD10 (see, for example, Ball et al., ). Also, some countries used other reporting mechanisms than ICD.…”
Section: Methodsmentioning
confidence: 99%
“…6 We extracted data for deaths where the primary or secondary cause of death was associated with accidental nonfire-related carbon monoxide poisoning using the following codes: ICD-10 codes X47 or ICD-9 codes E867, E868.0, E868.1, E868.2, E868.3, E868.8 or E868.9. 13 Extracted data also had to provide a supplementary code to characterize death associated with carbon monoxide poisoning using ICD-10 code T58 or ICD-9 code 986 related to the toxic effect of carbon monoxide. 10 Case definition for unintentional nonfire-related carbon monoxide poisoning was based on definitions used by the Centers for Disease Control and Prevention for carbon monoxide-related mortality, emergency department visits and hospital admission surveillance.…”
Section: Mortality Datamentioning
confidence: 99%
“…We defined a patient with CO poisoning as a participant who has been assigned diagnosis codes 986, E868, E952, or E982 according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) during hospitalization or a visit to the emergency department. The use of both ICD-9-CM of 986 and E-codes (including E868, E952, and E982) has been validated as an effective method to identify patients with CO poisoning 22 and adopted in many studies. 3,7,9,20,21 submit your manuscript | www.dovepress.com…”
Section: Definitions Of Variablesmentioning
confidence: 99%